Assessment of the Psychology of Private School Teacher’s with Reference to Motivation, Job Satisfaction, Performance and Organizational Commitment (International Journal of Innovative Research in Engineering & Management, 2021)
The role of psychology has increased over the  last few years. People have gone under extreme metal pressure  during COVID 19 pandemic. Lock down, quarantine, and deaths  of people have traumatised everyone. Suddenly the number of  academic researchers has turned to this issue. Several studies  have been conducted to understand the psychological issues  among people. Present study has focused upon the private  teachers in Delhi NCR. Researchers have clubbed 38 questions  related with teachers’ psychological aspects of private school  teachers. The questionnaire has been tested for reliability (Cronbach's Alpha 0.751). Further Factor analysis has extracted  04 components viz. Job Satisfaction, Motivation, Organizational  Commitment, and Employee Performance. Researchers have  found that there is significant difference in the opinion of teachers  about extracted psychological variables. The teachers are having  their opinion on a positive side even after the pandemic.  Researchers have found that teachers have adopted the changes  in the environment and feel satisfied with new normal.
Keywords: Work place motivation; Job Satisfaction; Organizational commitment